f(x)=4-2(x-6)^1/3 evaluate when f(x)=5

so I did this:

5=4-2(x-6)^1/3
1=-2(x-6)^1/3
(-1/2)=(x-6)^1/3

How do I get rid of the exponent 1/3? I am stumped.

1 answer

cube both sides
(an exponent of 1/3 means cube root, so what is the inverse of taking the cube root ?)

(-1/2)^3=[(x-6)^1/3]^3
-1/8 = x-6
x = 6-1/8
x = 47/8
Similar Questions
    1. answers icon 1 answer
  1. Evaluate Expressions PracticeComplete this assessment to review what you've learned. It will not count toward your grade. 3 of
    1. answers icon 1 answer
  2. Evaluate 4log(4)8Possible answers are: 4 0 8 1 Where do I start-I don't have an example to follow? Please give me a direction do
    1. answers icon 6 answers
    1. answers icon 1 answer
more similar questions